Economia solidária: a experiência de microcrédito e moeda social do Banco Palmas - Oliveira, José Cincinato de (2024)
This research was carried out through a case study of Banco Palmas, Palmeiras complex, Fortaleza/CE. As a methodology, exploratory research of academic works and publications on the subject and field research were adopted to explain, mainly, the dichotomy in the improvement of work and income in contrast to very low social indicators, including the worst HDI among the neighborhoods of Fortaleza. The study also aims to show how the solidarity economy can contribute to combating poverty and hunger in Brazil. This work started from the theoretical study on solidarity economy, adopting as a reference the work of Muhammad Yunus and the works of Paul Singer, with the aim of understanding how a community, such as the Palmeiras complex, managed to overcome so many adversities and have achieved many improvements in living conditions in that location. It was also assessed that some achievements imposed an increase in the cost of living and that people were not excluded from that community because the solidarity economy was adopted as an economic model. Structural achievements in the neighborhood such as: basic sanitation, treated water, electricity, schools, health centers, increased the monthly expenses of each family and, paradoxically, in a short time a significant part of residents migrated to other communities because they could not afford such expenses. In these circumstances, the organization of consumption and the granting of microcredit were essential in generating work, income and producing wealth. This strategy, therefore, contributed to families being able to take advantage of those achievements and continue living in the Palmeiras complex. Another important strategy was the adoption of a social currency that would allow the wealth produced in Palmeiras to circulate within the community, generating benefits for that society. However, such improvements did not produce an impact, in the same proportion, on some standards such as: Human Development Index – HDI, violence, education, among others. Thus, it can be inferred, from all these prerogatives, that improving people's income and/or their structural conditions are not sufficient requirements to raise some standards in a society.